EFFECT OF ORGANIZATIONAL JUSTICE ON STRESS WITH WORK-FAMILY CONFLICT AS A MEDIATING VARIABLE - SWANDARUJATI, MAXIMILIAN; NURFITRI, TITI; ANGGRAENI, ADE IRMA (INDONESIAN RESEARCH SOCIETY, 2019)
The purpose of this study is to analyze the influence of organizational justice on r stres with work-family conflict as mediating variable. There were 80 member chosen as respondent of the research by using purposive sampling method. This research using quantitative approach. Analysis tool used in this research is Multiple Regression with SPSS software. Based on the result of the analysis, it can be concluded that organizational justice has negative effect on stres with work-family conflict as a mediating variable.